Sub-National Formal Conflict Resolution Institutions in Ethiopia: The Case of South Nations, Nationalities, and People’s Region - Negash, Yideg Munana (Ethiopian Journal of Social Sciences, 2021)
After the collapse of the dictatorial regime in 1991, Ethiopia developed its first Federal Democratic Republic Constitution in 1995. Accordingly, the federation comprises ten regional states and two city administrations. The SNNP region is one among the founding member states of the federation. The region suffered from inter-ethnic disputes over various issues: identity, border, resource and cultural miscommunication. In the constitution, adopted by the Nations, Nationalities, and Peoples of the SNNPR, the Council of Nationalities was institutionalized with a number of constitutional mandates of which dispute management and resolution is the prominent one. Primary and secondary data had been collected for the accomplishment of the objective of the article. Thus, efforts and mechanisms the region used to deal with conflicts through formal conflict resolution institutions were analyzed. Hence, findings of this study showed that formal conflict resolution institutions (mainly the Council of Nationalities) of the region did not achieve what was expected from it. Conflict resolution responses of the region largely were not dynamic and systematically designed: deploying security force has been taken as a viable option to find out resort for conflicts emerged in the region. As a result, many conflict cases in the region remain unsettled. In fact the CoN had made some remarkable achievements that reinforce its future endeavor. As an institution which is found in a conflict prone region, the CoN should strengthen its instructional frameworks, skilled human power, modern technology, and desire to work with indigenous conflict resolution institutions to get things done.